The Effect of Live Interpretation with Theater on Attitudes and Learning of Children in the Mythbusters Exhibit. (July 2015) - Price, C. Aaron; Gean, Katherine; Barnes, Heather
<x content-type="archive" xml:space="preserve">Abstract</x> Mythbusters: The Explosive Exhibition is a traveling exhibit based on the popular television show. When housed at the Museum of Science and Industry, Chicago, it included a traditional, interactive free flow exhibition space followed by a live facilitated show. This paper describes results from an experimental study about the effects of the Live Show on the learning of and attitudes towards science. A pre-test was given to 333 children entering the exhibit. A post-test was given to 80 children after they walked through the free-flow portion of the exhibit and to 191 children after they watched the Live Show. Thirty-two children were interviewed in lieu of taking the post-test. Findings show additional knowledge and attitude gains by the children who watched the Live Show. However, no gains in either group were found on items related to recognizing terminology related to the scientific process.